The Power of Social Media: Shaping Risk Perception and Investment Decisions Among Young Equity Investors - Yoga, Ika; Hastuti, Rina; Pramesti, Wahyu; Rahmayati, Anim (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2025)
Purpose: This research study examines the pivotal role of social media in shaping risk perception and investment behavior among young equity investors. It focuses on the impact of social media content on their attitudes toward risk and the decision-making process in investments.Design/Methodology: This study applied the quantitative method using the survey technique to extract data from 250 young stock investors. The data was collected via questionnaires based on a semantic differential scale and analyzed using the SEM-PLS method in order to get complex relationships between the variables unraveled.Findings: Social media significantly shapes young investors' risk perceptions and investment behavior. It not only directly influences investment decisions but also mediates risk perception, leading to changes in investment behavior.Practical implications: This is crucial evidence that informs the place for social media in integrating financial literacy into education. The fact that young investors are supposed to make a critical analysis of any information brought to them is important for these programs of financial literacy. The potential biases and misguidance in the information that can be found on social media should be made known to the young investors in order to raise their level of decision-making.Originality/Value: This paper offers new insights into the impact of social media on young investors' behavior, highlighting risk perception as a key mediator. It also emphasizes financial literacy programs—such as workshops and gamified learning—to counter social media biases. Additionally, this study fills gaps in the literature by exploring how social media shapes risk perception and investment decisions